The synthesis, antimicrobial activity studies, and molecular property predictions of novel benzothiazole-2-thione derivatives - Berk, Barkın; Atlas Tahirovic, Yeşim; Bülbül, Emre Fatih; Biltekin, Sevde Nur (University of Istanbul, 2017)
Benzothiazoles and 2-mercaptobenzothiazoles are important classes of bioactive organic scaffolds possessing antibacterial, antifungal, antitubercular, antiinflamma-tory, antidiabetic, and antimalarial properties. In recent years, prediction of drug-likeness, molecular, absorption, distribution, metabolism, and excretion (ADME) properties using in silico techniques has become a standard procedure for the evaluation of molecules in terms of their potential clinical use. In this study, compounds structured 6-benzoyl-3-substitutedmethylbenzo[d]thiazole-2(3H)-thione were synthesized using the Mannich reaction starting from 2-mercaptobenzothiazole. The antibacterial and antifungal activities of these compounds were determined against Staphylococcus aureus, Escherichia coli, Enterococcus faecalis, Pseudomonas aeruginosa, Candida albicans, Candida krusei, and Candida parapisilosis using a broth microdilution method. An additional analysis was undertaken using the in silico technique to predict the drug-likeness, molecular, and ADME properties of these molecules. Among all the compounds, respectively, Compounds 1-4 and 6-11 exhibited good minimum inhibition concentration values against Staphylococcus aureus and Candida species with promising predicted properties.
Keywords: ADME; Antifungal; Benzothiazole-2-Thione; Candida Albicans; In Silico; Molecular Properties